Cancer incidence among pesticide applicators exposed to butylate in the agricultural health study (AHS) - Lynch, Shannon M. (2009)
Although limited, epidemiologic studies suggest possible associations between butylate use and cancer risk, specifically prostate cancer and non-Hodgkin lymphoma (NHL). We examined butylate use and cancer risk more broadly in the AHS, a cohort of licensed pesticide applicators in Iowa and North Carolina. Pesticide use information was collected using self-administered questionnaires. Poisson regression was used to calculate rate ratios(RR) and 95% confidence intervals(CI). Two exposure metrics were used: lifetime exposure days(LD) and intensity-weighted lifetime exposure days(IWLD). We used two referent groups: unexposed to butylate and the lowest butylate usage category. This analysis included 19,655 applicators with complete butylate use information; 5,297 applicators were exposed to butylate, making this the largest study of butylate to-date. The mean follow-up time since enrollment was 9 years. Prostate cancer risk was significantly elevated among applicators in the highest LD category in both referent groups (low exposed referent: RR(LD)=2.09,95%CI=1.27–3.44). We observed a significantly elevated joint effect of prostate cancer family history and high butylate usage across both exposure metrics and both referent groups (low exposed referent: RR(LD)=2.00, 95%CI=1.07–3.74), and a non-significant, elevated interaction between butylate use and prostate cancer family history, similar to a previous AHS finding. Statistically significant increased risks and exposure-response trends were seen for all lymphohematopoietic cancers (AL) and NHL for both exposure metrics and referent groups (low exposed referent: AL:RR(LD) =2.27, 95%CI = 1.18–4.37; NHL: RR(LD)=3.44, 95%CI =1.29– 9.21). Our analysis did not find meaningful associations for other cancers analyzed. Further study is warranted for AL, NHL and prostate cancers.